Analysis of Service Quality at Beauty Salon in Surabaya Using the ServQual Method - Kelvin; Sharon; Tjandra, Suhatati; Suhartono, Andri (Publisher Cv. Inara, 2023)
This research was conducted to analyze and determine service quality and supporting attributes and to find gaps or discrepancies between consumer expectations and perceptions to improve service quality and provide solutions to existing problems. Analysis of service quality is carried out using the Servqual Method (Service Quality), a method used to measure service quality. This Servqual method measures how well a service provided by a company/service is expected to be received. This Servqual method includes 5 Gaps with five attribute dimensions: Tangibles, Responsiveness, Assurance, Reliability, and Empathy. The data needed to analyze is by distributing questionnaires to customers and management. The results of distributing questionnaires to 27 respondents and the results of the analysis show that there is a gap between consumer expectations and the perceptions received. The most significant gap is in Gap 5 with the PS2 attribute -1.073, with repair solutions ensuring consumers are comfortable by inviting them to choose a comfortable seat. Gap 1 is on the TS1 attribute -0.215, so a solution is provided to ensure the cleanliness of the salon equipment used. Gap 2 is on the PS3 attribute -0.67 and is given a solution namely, staff must rearrange management service standards and ensure staff responds well to customers. Gap 3 on AS4 attributes -0.73 with improvement solutions, namely rearranging good service standards so that the advertisements promoted are appropriate, gap 4 there are two attributes that are not managed to fulfill, namely TS5 and TS6 so that suggestions for improvements were given to install automatic air fresheners in every corner of the room and look for the best internet network provider and increase internet network speed.